South African emergency medical service personnel perceptions of research and evidence-based practice - Dlamini, Zamasiba Cynthia (Division of Emergency Medicine, 2025)
Background: Evidence based practice (EBP) is the deliberate application of up to date, best available evidence to make decisions about health care. The implementation of EBP includes five steps: asking the right question, accessing relevant evidence, appraising evidence for reliability and validity, applying evidence to patient care, and lastly assessing clinical practice. The aim of this study was to assess strength of beliefs about EBP, and the frequency of implementation of EBP in South African emergency medical service (EMS) personnel. Methods: In this cross-sectional study we deployed an online survey of South African EMS personnel using two validated scales for measuring individual beliefs about EBP, their ability to implement it, and the extent of actual EBP implementation. Results: There were 67 respondents who were predominantly male (77,6%, n=52), had a mean age of 41,1 (± 9,8) years, and represented a wide range of operational, management and education experience. Measured by the EBP beliefs scale, respondents had a favourable attitude towards EBP (Median score: 60, IQR:51-69). There was no significant difference between the median beliefs score between qualification categories (p=0,578). Responses to the EBP implementation scale items indicate that respondents were not routinely implementing EBP. The median score was 21 (IQR: 8-37). The three EBP activities that were implemented most frequently were informally discussing evidence from a research study with a colleague (n=25), accessing the clinical practice guidelines (n=25), and promoting the use of EBP to colleagues (n=25). Availability of, and access to, appropriate evidence, and a perceived lack of critical appraisal skills, were identified barriers to EBP. In addition, the nature of the patient-provider relationship and the lack of feedback loops limits the application of EBP in EMS. Conclusion: The findings from this study indicate that respondents held favourable beliefs in EBP but identified several barriers to implementation of EBP. Supportive environments and training can facilitate the implementation of EBP principles in prehospital emergency medical care. Deidentified data is available upon request to the corresponding author for use in accordance with the participant consent obtained and pending appropriate ethical approvals.